Effect of paternal supplementation of palm oil (Tocotrienol Rich Fraction) on male fertility / Norzeila Sulaiman - Sulaiman, Norzeila (2015)
Infertility is a biological inability of an individual to conceive and half of the cases are related to male infertility. Tocotrienols, a component of vitamin E, demonstrated the ability to improve the functions of male reproductive system. This study was performed to investigate the anti-infertility effects of Tocotrienol Rich Fractions (TRF) from palm oil extract on male rat model. Fifteen male Wistar rats were randomly divided into 5 groups (n=3). Control negative group (F) was orally administered with distilled water (0.1 ml), control positive group (G) was orally administered with vitamin E-free corn oil (O.1ml) and treated groups were orally administered with three different concentrations of TRF, at a dose of 30 mg/kg (H), 60 mg/kg (I) and 90 mg/kg (J) respectively. After 7 days of acute treatment, the blood of the rats was collected using retro orbital sinus technique for biochemical investigation and hormonal analysis. The rats were sacrificed using cervical dislocation. The sperm were collected from cauda epididymis for analysis. TRF supplementation induced improvement in sperm morphology and motility compared to control negative group (F). In similar manner, TRF also provide positive effects to liver and renal function by reducing blood glucose and bilirubin level. Hormonal analysis demonstrated the ability of TRF to enhance LH production, which enhance spermatogenesis, thus helps in boosting fertility. This study suggested that TRF possesses the potential as anti-infertility agent and beneficial to the renal and liver function.